3D digital light process bioprinting: Cutting-edge platforms for resolution of organ fabrication - Jeong, Yun Geun; Yoo, James J.; Lee, Sang Jin; Kim, Moon Suk (Materials Today Bio, 2024)
Research in the field of regenerative medicine, which replaces or restores the function of human damaged organs is advancing rapidly. These advances are fostering important innovations in the development of artificial organs. In recent years, three-dimensional (3D) bioprinting has emerged as a promising technology for regenerative medicine applications. Among various techniques, digital light process (DLP) 3D bioprinting stands out for its ability to precisely create high-resolution, structurally complex artificial organs. This review explores the types and usage trends of DLP printing equipment, bioinks, and photoinitiators. Building on this foundation, the applications of DLP bioprinting for creating precise microstructures of human organs and for regenerating tissue and organ models in regenerative medicine are examined. Finally, challenges and future perspectives regarding DLP-based bioprinting, particularly for precision printing applications in regenerative medicine, are discussed.
Keywords: Bioink; Bioprinting; Cutting edges; Digital light process; High resolution; Medicine application; Printing equipments; Regenerative medicine; Resolution; Three-dimensional bioprinting; Bioinks; Bioprinting; Digital light process; Regenerative medicine; Resolution